Molecular Diagnosis of CoccidioidesPosadasii from Aborted Placenta of Ewes by RT-PCR - BushraHamza Fares; Ban A. Abdulmajeed; Hameed Abdulhussein Mejbel (Kufa Journal for Veterinary Medical Sciences, 2014)
Diagnosis of diseases depends on histology using formaldehyde-fixed paraffin embedded tissue .The polymerase chain reaction (PCR)helps the pathologists to confirm the diagnosis of many disease including mycotic infections.